ANALISIS PENGARUH KUALITAS PELAYANAN (SERVQUAL) TERHADAP KEPUASAN LANSIA DI PANTI BHAKI KASIH SITI ANNA PANGKALPINANG - Dolorosa Tea, Maria; Medinal; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2020)
The quality of service has an important role in business services. The purpose of this study is to find out the quality of services, namely tangible, reliability, responsiveness, assurance and empathy toward the satisfaction of the elderly in the Bhakti KasihSiti Anna Pangkalpinang orphanage. The approach used in this study is quantitative approach with the sampling technique used is purposive sampling. The method of data collection uses a questionnaire with 32 respondents. The analyzing of the data using multiple regression analysis techniques. The result of the study showed that he dimensions of services quality that tested together has a positive and significant effect on elderly satisfaction. This is proven by the F test where F count is 86.176> F table 2.85.